Penyuluhan Pengasuhan Efektif di Masa Bencana Melalui Parenting Education Berbasis Online - Wiwiek Zainar Sri Utami; Eneng Garnika; Luâ€™luin Najwa; Dewi Rayani; Lalu Ari Irawan (Jurnal Pengabdian UNDIKMA, 2020)
The purpose of this service activity is to provide the knowledge in education program handling for parents (parenting education) and teachers to increase their treasure of knowledge about children's growth and development and to align children's education at school and home during the Covid-19 pandemic. The method of this community service program was conducted through the online platform "Whatsapp special Groupâ€ for teachers and parents about the psychological impact of this pandemic to students, teachers, and parents; (1). how to manage negative emotions, online learning management for teachers, and how to construct effective communications between teachers and parents on children education. 2. Performing questions and answers session every the end of counseling material delivery. 3. Program evaluation of Parenting Education on an online basis and the continuity of program planning. The result of this program was well accepted and easy to understand by participants. Furthermore, during the program all participants were enthusiastic about discussion, sharing their knowledge and information between them and community service teams.